Global existence and energy decay of solutions to the Cauchy problem for a wave equation with a weakly nonlinear dissipation - Abbès Benaissa; Soufiane Mokeddem (Abstract and Applied Analysis)
We prove the global existence and study decay properties of the solutions to the wave equation with a weak nonlinear dissipative term by constructing a stable set in H1(ℝn).